“MOHON IZIN, MAS, MBAK”: WUJUD TUTURAN DAN KESANTUNAN BERBAHASA DALAM INTERAKSI RESIDEN - Kurniawati, Atin; Hanafi, Muchtar (IAIN Surakarta, 2024)
This article discussed the form of speech acts and language politeness in interaction among residents by focusing on the speeches containing the words